From formal analysis to artistic practice: The perception of the image and the form in the creative process - Palazón Cascales, Bartolomé (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Approach to the formal analysis of the image, from a perceptive and organizational point of view in the personal artistic process of the students who take the subject of Image and Form Analysis at the University of Zaragoza. Through the History of the Image, it is committed to practical studies that enable the understanding of the fundamentals of visual communication, from its aesthetic perspective, through the conscious appreciation of images and forms. Students open their minds to new perspectives, questions and other lines of research from various areas: cultural, social and artistic.